2009
DOI: 10.1159/000260040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Polihexanide-Preserved Wound Covering Gel on Dermal Wound Healing

Abstract: Objective: Daily wound assessment, including dressing changes and the removal of old ointments causes discomfort for the patient. We therefore developed a new thermoreversible and transparent gel formulation that allows for filling wounds of different shapes and depths. The aim of the study was to investigate the effect of a wound covering gel on wound healing and the skin’s microcirculation. Materials and Methods: Investigations were carried out in a standardized and reproducible wound model (hairless mice SK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
4
12
0
1
Order By: Relevance
“…Its transparency allows a direct assessment of the wound. Our previous studies as well as the data obtained from other groups showed excellent results concerning toxicity and wound healing in experimental and clinical setups .…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Its transparency allows a direct assessment of the wound. Our previous studies as well as the data obtained from other groups showed excellent results concerning toxicity and wound healing in experimental and clinical setups .…”
Section: Introductionsupporting
confidence: 59%
“…The purpose of this study was to examine the effects of polyhexanide ointment and chitosan solution on angiogenesis, epithelialisation and microcirculation in a standardised mouse model on fresh wounds . The wound model in hairless mice allows for qualitative and quantitative analysis of the wound microcirculation after topical application of different formulations and wound dressings .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data of the impact of wound gel on microcirculation and wound healing in mice in our research team showed no toxic effects [7] . Another study of our team found an integrity loss of the endothelium and a decrease in the functional vessel density after 1 hour of topical exposures in ears of mice [8] .…”
Section: Discussionmentioning
confidence: 94%
“…Flushing of deep wounds (e.g. bite injuries) with topically active strong protein-binding antiseptics is permissible only if drainage of the rinsing fluid is provided [11,33,[41][42][43][44][45] .…”
Section: The Role Of Polihexanide In Risk Woundsmentioning
confidence: 99%